If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = 3y + -3.5 Reorder the terms: 4y = -3.5 + 3y Solving 4y = -3.5 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 4y + -3y = -3.5 + 3y + -3y Combine like terms: 4y + -3y = 1y 1y = -3.5 + 3y + -3y Combine like terms: 3y + -3y = 0 1y = -3.5 + 0 1y = -3.5 Divide each side by '1'. y = -3.5 Simplifying y = -3.5
| x/-9=-8 | | 11x=24 | | 20x^2-60x-25=0 | | 2x^4-9x^3-2x^2=0 | | 106/2 | | x*x=106 | | (8x-5)+(22y)+(7x+3)=180 | | -w+8.5= | | -2x+4=-12-6x | | 64-9p=-3 | | y-2y=6 | | 2.8x=10.08 | | 9x^4-1=0 | | 9(2t-1)-13=t-(t+3) | | 9=3x+13 | | 8x-5+22y+7x+3=180 | | 2x-2y=64 | | 22-55x=14+3x | | 2x+2y=64 | | 22y+20x-30=180 | | 1/2x+1/4y=4 | | -8z^4+z=0 | | 1-y=15 | | 3/5a=a+5 | | 3x-y=64 | | -2x-10=x-18+3x | | 64-9p= | | 29+7d=5d+16 | | (y^2-4y-5)/(y^2-2y-15) | | 6a^2-4a(1-8a)= | | 4(2)-4y=24 | | -18-6k=-(1+3k) |